Preceramic polymer-derived ceramic foams with lamellar strut porosity. Issue 1 (July 2020) - Dammler, K; Schelm, K; Kniep, D; Hasemann, G; Scheffler, M
Abstract: Open porous replica foams with additional lamellar strut pores were prepared by preceramic polymer processing combined with a freeze-drying process. Polymer foam templates were coated with an aqueous polymethylsilesquioxane system followed by freezing at - 20 °C to generate hierarchical porosity within the foam struts. The cellular structure was preserved during freeze drying, cross-linking, template removal and pyrolysis, and additional strut porosity was formed. The size of the lamellar strut pores was found to depend on the solid load of the preceramic slurry and its pretreatment procedure. The cellular materials obtained in this work possess additional lamellar strut pore channels with a thickness of approximately 40 µm and a total foam porosity of > 90 %.